Primeras páginas de la Revista Perfiles de las Ciencias Sociales - Perfiles de las Ciencias Sociales, Revista (Perfiles de las Ciencias Sociales, 2019)
Primeras páginas de la Revista Perfiles de las Ciencias Sociales